News media and political contestation in the Somali territories: defining the parameters of a transnational digital public. Issue 1 (2nd January 2019) - Chonka, Peter
ABSTRACT: This article examines the extent to which different forms and technologies of media production facilitate popular participation in a 'digital public' across the politically fragmented Somali territories. Based on textual analysis of local media and comparative examination of news production and consumption, the article emphasises the dual character of the public sphere in the Somali context. Here, local media production centred in individual capitals of different political administrations coexists and overlaps with a transnational arena of Somali-language broadcasting and debate from various externally-based media networks. In this distinctive Somali media ecology, multiple forms of 'old' media intersect with digital technologies that have emerged throughout the post-1991 period of statelessness, conflict and political reconfiguration. Local public spheres of media production and public engagement help create state-like identities and political imaginaries. Nonetheless, these are articulated in the wider transnational Somali-language digital public that such administrations have limited ability to control. In this context certain notions of a transnational Somali ethnolinguistic or religio-cultural community are maintained not in spite of conflict and fragmentation, but rather as a result of a media ecology and digital public that itself exists as an outcome of political instability and flux.